Chromatographic and Thermal Characteristics, and Hydrolytic and Oxidative Stability of Commercial Pomegranate Seed Oil - Marta Siol; Agnieszka Dudek; Joanna Bryś; Diana Mańko-Jurkowska; Eliza Gruczyńska-Sękowska; Sina Makouie; Bharani Kumar Palani; Marko Obranović; Piotr Koczoń (Foods, 2024)
The current investigations were aimed at the determination of the hydrolytic and oxidative stability of commercial pomegranate seed oils provided by four different producers, and to assess the oils’ primary quality parameters. During storage, many changes occur in oils that can significantly affect their quality. The oils were tested for acid and peroxide values, fatty acid profile, and their distribution between the sn-1,3 and sn-2 positions of triacylglycerols. The oxidative stability was also determined, and melting curves were plotted for the oils. The analyzed oils were stored for one month in a dark place at refrigerator temperature. Based on the obtained results, it was found that the acid values for most oils did not exceed the permissible level determined by the Codex Alimentarius. However, in all oils, the peroxide value exceeded the permissible level set by the standard EN ISO 3960:2017-03 and the Codex Alimentarius after the one-month storage period. The examined pomegranate seed oils were found to be valuable sources of polyunsaturated fatty acids, especially punicic acid, which was the most abundant fatty acid present in these oils. In all analyzed oils, linoleic acid predominated in the sn-2 position of the triacylglycerols. Pomegranate seed oils did not exhibit good oxidative stability, as the oxidation induction times for all tested oils were very short. The storage period significantly affected the content of the primary oxidation products and oxidative stability of the oils.